Cat flea (Ctenocephalides felis) infestation in quarantined marsh deer (Blastocerus dichotomus) populations - Szabo, MPJ; Matushima, E. R.; Pereira, M. D.; Werther, K.; Duarte, JMB (Amer Assoc Zoo Veterinarians, 2000)
Marsh deer (Blastocenrs dichotomus) were captured for a research progam in Brazil and maintained in quarantine stations. After 60 days, fleas were detected on animals and identified as Ctenocephalides felis felis. Elimination of the infestation was difficult. Animal treatment with a fipronil-based compound was effective, and subsequently captured animals were treated prophylactically. Some animals remained infested, and some died from the infestation.
Keywords: flea; Ctenocephalides felis; marsh deer; Blastocerus dichotomus; outbreak; infestation